A flower shape-green synthesis and characterization of silver nanoparticles (AgNPs) with different starch as a reducing agent - Khanittha Ponsanti (Journal of Materials Research and Technology, 2020)
This work aims to study the synthesis of flowers shaped silver nanoparticles (AgFLs) with green method by using corn starch (Co-S), cassava starch (Ca-S) and sago starch (Sa-S). The starch acts as a reducing agent in synthesis of silver nanoparticles and contains glucose by reducing silver ions from silver nitrate as silver nanoparticles. The silver nanoparticles were characterized by using Transmission electron microscopy (TEM), X-ray diffraction (XRD), UV–vis spectrophotometer, Fourier transform infrared (FTIR), Thermogravimetric (TGA) and Particle size analyzer. TEM images show the shape of synthesized silver nanoparticles as flowers-like and particle size distribution of synthesis of silver nanoparticles from corn starch, cassava starch and sago starch in the range of 47.8 nm, 107.5 nm and 118.9 nm respectively. The X-ray diffraction patterns indicated that silver nanoparticles had face-centred cubic (fcc) structure. The UV–vis spectroscopy shows the maximum absorption of silver nanoparticles at 420–430 nm. Therefore, synthesized silver nanoparticles with different starch were of flower-shape. Moreover, the size of flower- shape silver nanoparticles from by corn starch was smaller particle distribution than that of cassava starch and sago starch.